Kajian Umum Rumah Panggung Walewangko Minahasa Sulawesi Utara - Doly Herling Tiagas (Fakultas Teknik Universitas Cenderawasih, 2025)
Rumah Panggung Walewangko is a traditional traditional house of the Minahasa tribe in North Sulawesi which is artistic and needs to be preserved. Overall, this house is made of hard and sturdy wood. This research reviews the general shape and materials used with the aim of providing more detailed information. This method is carried out by conducting studies from several literature and references. From this research, it was concluded that the Walewangko stilt house needs to be preserved by continuing to support its construction because it has the ability to withstand earthquakes, is practical, natural, and costs less to build than a brick/wall house.